A Computer-Aided Design System (FBAR) to Solve Four-bar Coupler Position Problems - Gudavalli, Ram Maruti (My University, 1979)
A computer-aided design system (FBAR) has been developed which is capable of solving four-bar coupler position problems. This system can handle theoretically any number of positions of the coupler link and allows the designer to exercise his judgement in the design process by making use of the computer and the graphical display.
The theory is based on a multifactor optimization of two dependent design variables (errors in the coupler point coordinates and in the coupler link orientation) and by imposing constraints to ensure that a proper four-bar mechanism is obtained.
At present the synthesis program of the system is run on a CDC 6400 computer in a timesharing mode and the graphical analysis program is run on a PDP11/34 mini-computer. The final aim would be to make it a single system through a satellite graphics approach.
FBAR, the software system, has been tested for all types of the four-bar mechanisms (i.e., crank-rocker, double-crank and double-rockers) with the number of prescribed positions of the coupler link varying from three to nine.
Keywords: Mechanical Engineering; Mechanical Engineering